Clinical implications of restrictions in criteria for defining surgical site infections after mastectomy. (17th June 2021) - Bediako-Bowan, Antoinette A. A.; Warren, David K.; Nickel, Katelin B.; Fraser, Victoria J.; Olsen, Margaret A.
Abstract: More than 50% of women with clinically apparent infection after mastectomy did not meet the 2020 National Healthcare Safety Network (NHSN) definition for surgical site infection (SSI). Implant loss was similar whether the 2020 NHSN SSI definition was met or not, suggesting equivalent adverse outcomes regardless of restriction to the surveillance definition.